Principles of Entrepreneurship (ENT530): Social Media Portfolio: Cookies Crunch / Nurul Syazwani Saiful Bahari - Saiful Bahari, Nurul Syazwani (2021)
Cookies Crunch is a small business that has to introduce by myself. I plan the businesses through an online platform for advertising and selling. My products are more focused on quality to the customer. The admin for the online business is me named, Nurul Syazwani Binti Saiful Bahari. We cover up cash on delivery in Kuantan, Pahang area while the others we sent through shipping. Cookies Crunch offers to the customer crunchy and soft cookies for the sweet tooth and cookies lover. Our target market is individuals who love cookies range age from kids to elderly. What the best is, our taste feels like which makes the customer satisfied. at the end of the summary, I hope my small business will grow and expend more further in the future and more and we will provide a lot of delicious flavours that can satisfy more customer.